2008
DOI: 10.1590/s0103-84782008000700001
|View full text |Cite
|
Sign up to set email alerts
|

Atividade inseticida de meliáceas sobre Diabrotica speciosa (Col., Chrysomelidae)

Abstract: IIAtividade inseticida de meliáceas sobre Diabrotica speciosa (Col., Chrysomelidae) Palavras-chave: Melia azedarach, plantas inseticidas,Cucumis sativus, Phaseolus vulgaris. ABSTRACT Diabrotica speciosa is a polyphagous insect-pest and its control demands a great deal of insecticides applications. The use of extracts from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…these effects in different host plants. Seffrin et al (2008a) observed that aqueous extracts of different M. azedarach plant structures successfully controlled D. speciosa adults in cucumber and snap beans; however, extract-treated plants did not have their height and yield affected. Furthermore, Seffrin et al (2008b) reported that M. azedarach leaflet extract caused stronger antifeeding effect on D. speciosa adults than the petiole + stem extract.…”
Section: Larvaementioning
confidence: 99%
“…these effects in different host plants. Seffrin et al (2008a) observed that aqueous extracts of different M. azedarach plant structures successfully controlled D. speciosa adults in cucumber and snap beans; however, extract-treated plants did not have their height and yield affected. Furthermore, Seffrin et al (2008b) reported that M. azedarach leaflet extract caused stronger antifeeding effect on D. speciosa adults than the petiole + stem extract.…”
Section: Larvaementioning
confidence: 99%
“…Métodos de controle alternativo de insetos-praga sem que haja aplicação de agrotóxicos têm sido testados em consequência da crescente utilização de alimentos orgânicos, e também com a preocupação com o meio ambiente e a saúde humana (vendraMiM & CaStiGlioni 2000). Em termos de agricultura orgânica são empregados produtos alternativos, como raiz de taiuiá (StüPP et al 2006), óleo de nim (Seffrin et al 2008), extratos aquosos de fumo, pitangueira, cinamomo e alho (MaChado et al 2007). Sedorko et al (2010) ao realizarem testes com oito atrativos preparados a partir de óleos essenciais comerciais, com intuito de propor uma alternativa para o controle de moscas-da-fruta (Diptera: Tephritidae) notaram que, dos 422 insetos capturados no experimento, 21% eram da espécie D. speciosa, atraídas por citronela (Cymbopogon sp).…”
Section: E-issn 1983-0572unclassified